Transparency of Space in Contemporary Japanese Architecture - Konovalova, Nina (project baikal, 2018)
In some fundamental categories of Japanese culture, which are used for preserving and updating traditions in contemporary architecture of the country, "transparency" takes a special place. "Space transparency" denies the idea of boundary or barrier in architecture. In modern Japanese architecture, the "transparency" of space is emphasized and enhanced by its emptiness. In the content of the "transparency" concept in the European consciousness and in the Japanese one, some fundamental differences can be found. If the European mentality associates "transparency" with something illusory and ephemeral, and such qualities are inherent in the image of modern architecture of the West, in Japan "transparency" is perceived as clarity, accuracy, ambiguity, so "transparent architecture" receives a range of artistic and figurative-symbolic techniques, that give architecture a new quality.